Effect of alternating current (AC) stressing on the microstructure and mechanical properties of low-silver content solder interconnect. (January 2019) - Zhu, Ze; Chan, Yan-cheong; Wu, Fengshun
Abstract: The low-cost low-silver-content solder is receiving high attention while its reliability is not well studied. In this work, a copper/tin-silver-copper/nickel (Cu/Sn0.3Ag0.7Cu/Ni) line-type solder interconnect was designed for investigation of the effect of alternating current (AC) on the microstructure and mechanical properties. Three dimensional (3D) X-ray microcomputed tomography tests showed voids and protruding IMCs formed in the solder/Ni and solder/Cu interface regions of the interconnect after prolonged AC stressing, respectively. The thickness growth of interfacial IMC layers followed linear laws with faster rates than those in thermal aged sample. Atomic migration of Cu atoms in Sn0.3Ag0.7Cu solder was estimated using mathematical models with a thermal gradient of 206.77 °C cm −1 . Significant degradation in mechanical properties happened. Nano-indentation results showed the hardness and elastic modulus in different solder areas were in the following order: central solder > solder near solder/Ni interface > solder near solder/Cu interface. Four mechanisms can be used to explain these results of AC damages: 1) elevated temperature due to Joule heating, which enhanced grain coarsening and dislocations redistribution; 2) thermal fatigue due to cyclic loading, which damaged the interconnect strength by accumulated stress induced by mismatch in the coefficients of thermal expansion; 3) thermo-migration due to thermal gradient from Ni side to Cu side, which released the thermal stress at the solder/Ni interface and prevented further deterioration, while increasing the thermal stress at the solder/Cu interface and deteriorated the mechanical strength; 4) atomic migration due to chemical gradient, which induced the mass redistribution and contribute to the growth of IMCs layers. Highlights: Effect of AC on interconnects was studied using 3D xCT, SEM and nano-indenter. Interfacial IMC layers grew linearly under AC stressing. Voids and cracks formed at the interfaces under AC stressing. Damage mechanisms of AC were a mixture of Joule heating, thermal fatigue, chemical gradient and TM.